Exploring EFL Lecturer’s Strategies and Challenges in Teaching Critical Listening for the Third-Semester Students of English Education Study Program at PGRI University of Palembang: English - Nyimas Maynisa Aulia; Tahrun; Masagus Firdaus (Journal of English Development, 2024)
This study aimed at determining:(1) strategies in teaching Critical Listening; (2) implementation of strategies in teaching Critical Listening; (3) challenges in teaching Critical Listening; (4) solutions for teaching Critical Listening. This study was a qualitative using case study method. The respondent was the lecturer of Critical Listening. Data collection technique were observation, interview, questionnaire and documentation. Data analyses technique were data collection, data display, conclusion and review. The findings showed that (1) strategies used were Bottom-Up and Top-Down, and Direct Strategy. (2) this strategies used to guide students comprehend meanings from audio, understand vocabularies, know the outline of conversation from audio, build students’ confidence in sharing their critical thoughts about topics. (3) challenges were time allocation, unsupported media, lack of understanding vocabularies, students’ low motivation in improving listening skill. (4) solutions were manage time allocation, improving learning environment of listening skill, adapting, improving students’ vocabularies and using various strategies.